The Effects of Natural Boron Mineral on the Essential Oil Ratio and Components of the Spearmint (Mentha spicata L.) - Hasan Basri Karayel (Journal of Agricultural Sciences)
This study was carried out to determine the effects of boron mineral on the essential oil ratio and quality in spearmint (Mentha spicata L.) species. Different boron doses (0, pure and 1/2 dose, 1/8 dose (8 L decare-1)) were applied in this study, but no measurement could be take due to plant death in the pure dose and 1/2 dose. The essential oils of spearmint harvested at two different time were obtained by the method of hydro-distillation. In the analyses by GC_MS/FID (Gas Chromatography/Mass Spectrometry - Flame Ionization Detector), the essential oil ratio based on boron doses was measured as 1.25% for the boron-free condition and 2.22% for the 1/8 dose, the main essential oil components were a total of 35 components in the leaves (without boron), and 29 components for the 1/8 dose. The main essential oil components obtained from the leaves (without boron) were Carvone by 55.12%, Limonene by 9.99%, 1,8-cineole by 8.81% while those for the 1/8 dose were Carvone by 56.02%, Limonene by 14.22%, 1.8-cineole by 6.79% in the first harvest. The essential oil components were found to be rich in terms of terpenes. In this study, which is the first study in which boron mineral was applied to spearmint with the application of boron mineral in solution form, the recommended dose for spearmint was found to be 1/8 boron dose.